2017
DOI: 10.1162/jocn_a_01023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anterior Cingulate Cortex in the Affective Evaluation of Conflict

Abstract: An influential theory of anterior cingulate cortex (ACC) function argues that this brain region plays a crucial role in the affective evaluation of performance monitoring and control demands. Specifically, control-demanding processes such as response conflict, are thought to be registered as aversive signals by the ACC, which in turn triggers processing adjustments to support avoidance-learning. In support of conflict being treated as an aversive event, recent behavioural studies demonstrated that incongruent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 56 publications
4
56
0
Order By: Relevance
“…In one study, the amplitude of the ERN was associated with the extent to which mistakes prime the processing of negative, but not positive, words (Aarts et al, 2013). In a conceptually similar fMRI study, reduced aMCC response to negative images occured after conflicting Stroop trials, while aMCC responses to positive images was reduced after congruent trials (Braem et al, 2016). These findings suggest repetition suppressionwhere the presentation of a given stimulus category (e.g., cognitive conflict) leads to reduced neural reactivity to the subsequent presentation of a similar stimulus (e.g., negative images).…”
Section: The Amcc and Valenced Responses To Conflictmentioning
confidence: 96%
“…In one study, the amplitude of the ERN was associated with the extent to which mistakes prime the processing of negative, but not positive, words (Aarts et al, 2013). In a conceptually similar fMRI study, reduced aMCC response to negative images occured after conflicting Stroop trials, while aMCC responses to positive images was reduced after congruent trials (Braem et al, 2016). These findings suggest repetition suppressionwhere the presentation of a given stimulus category (e.g., cognitive conflict) leads to reduced neural reactivity to the subsequent presentation of a similar stimulus (e.g., negative images).…”
Section: The Amcc and Valenced Responses To Conflictmentioning
confidence: 96%
“…Interestingly, this same area also becomes active when errors and other aversive signals are observed [22][23][24]. Thus, the ACC responds similarly to cognitive conflict and negative affect, possibly registering both as aversive signals [25][26]. …”
Section: Introductionmentioning
confidence: 99%
“…The source localization analysis suggests that these modulations of the N2 are associated with the anterior cingulate cortex (ACC). This region, and the medial frontal cortex in general plays a major role for inhibitory control (Huster et al, 2013); and has been suggested to orchestrate the connection of perception and action (Cavanagh and Frank, 2014) due to its hub-like structural and functional connection to sensory and motor areas (Braem et al, 2017;Bush et al, 2000). Corroborating this, it has been shown that the N2 reflects a concomitant coding of stimulus and response-related aspects likely, mediating the binding between stimulus and response features (Chmielewski et al, 2018;Folstein and Van Petten, 2008).…”
Section: Discussionmentioning
confidence: 97%